Depression and its associated factors among people with multidrug‐resistant tuberculosis in Myanmar. Issue 9 (24th June 2021) - Theingi, Phyo; Kamiya, Yasuhiko; Myat Moe, Myat; Cho San, Cho; Cox, Sharon E.
Abstract: Background: Depression is an important potential comorbidity in persons with tuberculosis (TB), yet data in many settings are scarce. Objective: To estimate the prevalence and risk factors of depression in persons with multidrug‐resistant tuberculosis (MDR‐TB) in Myanmar. Methods: A cross‐sectional survey among MDR‐TB participants at Aung San MDR‐TB treatment centre in Yangon during routine clinic follow‐up visits. Patients Health Questionnaire‐9 (PHQ‐9) in the local language was used to screen for depression and structured questionnaires conducted. Univariable and multivariable logistic regression models were performed to identify associations. Results: Three‐hundred and twenty‐nine participants were enrolled between 19th December 2019 and 31st January 2020; 33% (111/329) in the intensive treatment phase. The prevalence of depressive symptoms (PHQ‐9 ≥ 10) was (34/329) 10.33%. Multivariable analysis indicated financial hardship as a result of MDR‐TB symptoms/treatment (aOR = 2.63, 95%CI: 1.12–6.67), suffering ≥1 respiratory symptoms (aOR = 6.72, 95%CI: 2.41–18.76), high education level (aOR = 4.26, 95%CI: 1.70–10.70), reported diabetes (aOR = 3.05, 95%CI: 1.16–7.99) as associated with depressive symptoms, with weak evidence of an association in females (aOR = 2.09, 95%CI: 0.94–4.65). Conclusion: Depressive symptoms are more common in those with comorbidities/TB symptoms. Further research is required to determine the effects of interventions to support persons with depressive symptoms identified using simple, standardised validated tools like PHQ‐9.